Beyond the Diagnosis: Lived Experiences of Persons with Spinal Cord Injury in a Selected Town in Ghana - Abdul-Ganiyu Fuseini; Patience Aniteye; Afizu Alhassan (Neurology Research International)
Background. Although several studies have been conducted on the lived experiences of persons with spinal cord injury (SCI) in high income countries, there is no published data on such experiences in Ghana. The purpose of this study was to explore the lived experiences of persons with SCI in the Tamale Metropolis of the Northern Region of Ghana. Material and Methods. A qualitative descriptive design involving thirteen participants was conducted at the Tamale Metropolis-Ghana. A purposive sampling technique was used to recruit participants, using the Neurosurgical Unit of the Tamale Teaching Hospital as an outlet for recruitment of the sample. Data was gathered mainly through face-to-face in-depth interviews. The data was analyzed concurrently with data collection, using thematic content analysis. Ethical approval was obtained for the study from the Noguchi Memorial Institute for Medical Research and the research unit of the Tamale Teaching Hospital. Results. The three main themes that emerged from the data during analysis were “physical effects,” “psychological effects,” and “social issues.” Conclusion. The findings from the study suggest that SCI is a life threatening condition and that persons with SCI grapple with a myriad of physical symptoms that range from chronic pain and paralysis of lower and/or upper limbs, to bladder and bowel incontinence. These physical symptoms have significant psychological and social effects on the functioning of the affected persons.